Comparative antibacterial activity of 2D materials coated on porous-titania. Issue 32 (29th July 2021) - Mazinani, Arash; Rastin, Hadi; Nine, Md Julker; Lee, James; Tikhomirova, Alexandra; Tung, Tran Thanh; Ghomashchi, Reza; Kidd, Stephen; Vreugde, Sarah; Losic, Dusan
Abstract : Antibacterial activity of selected 2D materials on porous-titania prepared by plasma electrolytic oxidation (PEO) is presented. Abstract : Plasma electrolytic oxidation (PEO) is a well-established technique for the treatment of titanium-based materials. The formed titania-PEO surface can improve the osseointegration properties of titanium implants. Nevertheless, it can not address bacterial infection problems associated with bone implants. Recently, 2-dimensional (2D) materials such as graphene oxide (GO), MXene, and hexagonal boron nitride (hBN) have received considerable attention for surface modifications showing their antibacterial properties. In this paper, a comparative study on the effect of partial deposition of these three materials over PEO titania substrates on the antibacterial efficiency and bioactivity is presented. Their partial deposition through drop-casting instead of continuous film coating is propsed to simultaneously address both antibacterial and osseointegration abilities. Our results demonstrate the dose-dependent nature of the deposited antibacterial agent on the PEO substrate. GO–PEO and MXene–PEO samples showed the highest antibacterial activity with 70 (±2) % and 97 (±0.5) % inactivation of S. aureus colonies in the low concentration group, respectively. Furthermore, only samples in the higher concentration group were effective against E. coli bacteria with 18 (±2) % and 17 (±4) % decrease in numbers of colonies for hBN–PEO and GO–PEO samples, respectively. Moreover, all antibacterial samples demonstrated acceptable bioactivity and good biocompatibility, making them a considerable candidates for the next generation of antibacterial titanium implants.